(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of the intellectual achievements and cultural contributions of the great scholars who emerged during the 9th to 12th centuries in Movarounnahr and Khurasan, regions that were central to the flourishing of Islamic civilization. It examines the diverse array of disciplines in which these scholars excelled, including mathematics, astronomy, medicine, philosophy, theology, literature, and Islamic jurisprudence. Through meticulous research and analysis, the article sheds light on the innovative ideas, groundbreaking discoveries, and enduring legacies of figures such as Al-Farabi, Avicenna (Ibn Sina), Al-Biruni, Al-Khwarizmi, and Omar Khayyam, among others. Moreover, it explores the socio-cultural contexts and intellectual exchanges that facilitated the flourishing of knowledge and scholarship in Movarounnahr and Khurasan during this Golden Age of Islamic civilization, highlighting the pivotal role of these regions in the transmission of knowledge between East and West.